Analysis of the Implementation of Individual Counseling by Counseling Guidance Teachers with the CBT Approach to Overcome Student Delinquency Problems in Schools - Netrawati Netrawati; Neviyarni Neviyarni; Yarmis Syukur; Dina Sukma (Universitas Negeri Padang, 2021)
This study aims to prevent juvenile delinquency behavior by developing a counseling model of cognitive behavioral therapy (CBT). The problem of counseling skills for counseling teachers is an interesting study to do because in the industrial revolution era there were many problems for adolescents. The counseling model of cognitive behavioral therapy (CBT) is important to train teachers BK because this counseling model has a problem-solving focus on cognitive restructuring compared to other counseling models and approaches. The development of this model training was carried out for BK Teachers at SMP and SMA Padang Panjang. Based on the results of the descriptive analysis that has been carried out, it shows that the implementation of individual counseling by BK teachers with the CBT approach is generally in the medium category with an achievement of 74.6%. Furthermore, the implementation of individual counseling by BK teachers with the CBT approach is in the high category with an achievement of 17.6% and a small proportion is in the low category with an achievement of 5.9%. The results of this analysis illustrate that, the implementation of individual counseling by BK teachers with the CBT approach still needs to be developed.